The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1159/000448046
|View full text |Cite
|
Sign up to set email alerts
|

Infra-Conus Single-Level Laminectomy for Selective Dorsal Rhizotomy: Technical Advance

Abstract: Background/Aims: Selective dorsal rhizotomy for spastic cerebral palsy is an effective and well-validated surgical approach. Multiple techniques have been described in the past including multiple laminectomies and a single-level laminectomy at the level of the conus. There is considerable technical challenge involved with a single-level laminectomy approach. Methods: We report here a modification of the single-level laminectomy that selectively analyzes each individual nerve root with electromyography to separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…With the reduction of muscle tone of spastic muscles on their affected lower limbs, their motor function improved dramatically after post-op rehabilitation therapy. Spasticity of lower extremities in spastic diplegic and quadriplegic cases usually affects muscles of adductor, hamstring, gastrocnemius, and soleus with bilateral involvement in a varied degree [3][4][5][6]. Besides the spasticity found in these major muscles, muscle tone prominent increase in rectus femoris is observed as well in some of spastic CP children.…”
Section: Discussionmentioning
confidence: 99%
“…With the reduction of muscle tone of spastic muscles on their affected lower limbs, their motor function improved dramatically after post-op rehabilitation therapy. Spasticity of lower extremities in spastic diplegic and quadriplegic cases usually affects muscles of adductor, hamstring, gastrocnemius, and soleus with bilateral involvement in a varied degree [3][4][5][6]. Besides the spasticity found in these major muscles, muscle tone prominent increase in rectus femoris is observed as well in some of spastic CP children.…”
Section: Discussionmentioning
confidence: 99%
“…The use of Park's method could allow SDR to be performed via a single-level approach, particularly in cases with moderate or severe spasticity [2][3][4][5][6][7][8]. In an attempt to find a universally applicable EMG interpretation scheme that could be applied to all kinds of spastic CP cases (including mild ones), Browd developed a new rhizotomy protocol in 2016 [10]. In addition to applying the EMG response grading system, Browd's rhizotomy scheme also took preoperative assessment results (identifying the "target muscle" in CP cases before SDR) into account when EMG responses were interpreted during surgery [9,10].…”
Section: History Of Ionm-guided Sdrmentioning
confidence: 99%
“…Studies have shown that different anesthetics can affect intraoperative electrophysiological outcomes [16][17][18], including changes in threshold, latency to stimulus, and EMG response patterns. Because, to date, there is no proven anesthetic protocol used specifically for SDR, clinical practitioners have either just applied those protocols conducted in other neurosurgical procedures requiring IONM or simply developed their own [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Anesthesiamentioning
confidence: 99%
See 2 more Smart Citations